Why did Tiger Woods shoot 82? A commentary on Toner and Moran (2015). (January 2016) - Wulf, Gabriele
Abstract: In a recent article, Toner and Moran (2015) argued that athletes need to pay conscious attention to body movements, and that an external focus of attention would not be effective for continued improvement at the elite level. Their arguments appear to be based on misunderstandings of the attentional focus literature. In this commentary, I clarify that adopting an external focus does not imply that performers are not aware of their body movements. Rather, an external focus (i.e., focusing attention of the intended movement effect) refers to the preparation of movement execution. I maintain that an external focus is necessary to optimize performance and learning at any level of performance.